Gambaran Tingkat Pengetahuan Pasien DM tipe II tentang Manajemen DM di RSUD Wangaya Kota Denpasar - Daryaswanti, Putu Intan; Dwipranata, Kadek Yoga; Deani, Ni Wayan (Akademi Keperawatan Kesdam IX/Udayana, 2019)
Background: Diabetes Militus is a degenerative disease caused by changes in lifestyle such as diet can play a role in increasing blood glucose levels. This change in lifestyle is due to a lack of patient knowledge about DM management, leading to failure in DM management and complications for type II DM. Purpose: a study to determine the level of knowledge of Type 2 Diabetes Militus patients in Wangaya District Hospital, Denpasar. Method: The method used in the study is to use descriptive methods. The study population was patients visiting the Wangaya Hospital Polyclinic in Denpasar City with medical diagnosis of type II DM. The research sample of 30 respondents with purposive sampling. The data obtained from the questionnaire that had previously been tested for validity and reliability. Then the data is analyzed univariately to see the patient demographic characteristics and is presented in the frequency distribution. Results: the results of the study obtained the level of patient knowledge about management of Type 2 DM (73.3%) in either category. When viewed by the DM management component, the patient's knowledge of DM (63.3%) is sufficiently knowledgeable, the patient's knowledge of diet (63.3%) is good, the DM patient's knowledge of medicine (90.0%) is well-informed and knowledgeable DM patients about physical exercise (60.0%) lack knowledge. Conclusion: knowledge of type II DM patients about DM management as a whole is well known, but when elaborated the components of DM management which consist of the concept of disease from type II DM, diet, medication and physical exercise are not fully well known.